(68Ga)-PSMA-PET/CT for the detection of postoperative prostate cancer recurrence: Possible implications on treatment volumes for radiation therapy TEP-scanographie avec l'antigène membranaire spécifique de la prostate marqué au gallium 68 pour le suivi postopératoire du cancer de la prostate: implications possibles sur les volumes de la radiothérapie - De Bari, B.; Mazzola, R.; Aiello, D.; Aloi, D.; Gatta, R.; Corradini, S.; Salgarello, M.; Alongi, F. (Cancer Radiotherapie, 2019)
Purpose: The aim of this study was to define the pattern of relapse of postoperative prostate cancer in patients by using 68Ga-labeled prostate-specific membrane antigen positron-emission tomography/computed tomography ([68Ga]-PSMA PET/CT). Material and methods: Forty patients received a (68Ga)-PSMA PET/CT for biochemical failure. Following the Radiation Therapy Oncology Group (RTOG) guidelines, the pelvic clinical target volume has been contoured. Bone metastases were considered as outside the clinical target volume. Two subgroups of patients were defined, patients having relapse: (1) inside, or (2) outside the clinical target volume. Results: Globally, eight patients out of 32 presented with a positive lymph node failure inside the clinical target volume according to RTOG guidelines (25%), 22 patients had nodal relapses outside this clinical target volume (68.75%) and in two patients nodal relapses occurred both inside and outside of the clinical target volume (6.25%). Overall, 36 positive lymph node lesions were identified: of these, 23 nodal relapses were identified within the clinical target volume contoured according to RTOG and/or at the lomboaortic level (63%). To cover 95% of these 23 relapses, a hypothetical clinical target volume should encompass the nodal regions of the RTOG-defined clinical target volume as well as the paraaortic lymph node level up to T12-L1. Conclusion: Most of the patients in the present study, presented with distant lymph node and/or bone metastases. Therefore, larger target volumes should be adopted to treat at least 95% of lymph node regions at risk for an occult relapse.
CRIS-Team Scopus Importer:2025-10-13
Keywords: (; Prostatectomy; Prostatic cancer; Radiotherapy